Ontologi Ilmu Pengetahuan - Ermida Ermida; Ardimen Ardimen (Departement of Mathematics Education, 2023)
Ontology is a science that examines what is the nature of science or scientific knowledge which is popularly known by many people as science, what is the nature of rational truth or deductive truth and empirical reality that cannot be separated from science's perception of what and how. The ontology of science limits itself to scientific studies that humans can think about rationally and can observe through the five human senses. Meanwhile, the study of objects of study that are within the limits of pre-experience (such as human creation) and post-experience (such as heaven and hell) becomes an ontology of other knowledge outside of science. In language, ontology comes from the Greek word origin is